Foundations of complex systems : nonlinear dynamics statistical physics, information and prediction - Nicolis, G., 1939- (World Scientific, 2007)
A geometric process is a simple monotone process that was first introduced by the author in 1988. It is a generalization of renewal process. This book captures the extensive research work on geometric processes that has been done since then in both probability and statistics theory and various applications. Some results are published for the first time. A reference book for researchers and a handbook for practioners, it is also a useful textbook for postgraduate or senior undergraduate students.